ScATG8 Gene Cloned from Desert Moss Syntrichia caninervis Exhibits Multiple Stress Tolerance - Ting Cao; Yakupjan Haxim; Xiujin Liu; Qilin Yang; Amangul Hawar; Abdul Waheed; Xiaoshuang Li; Daoyuan Zhang (Plants, 2023)
Syntrichia caninervis is the dominant species of biological soil crust in the desert, including the Gurbantunggut Desert in China. It is widely distributed in drylands and considered to be a new model of vegetative desiccation tolerance moss. Here, we cloned an ATG8 gene from S. caninervis and confirmed its function under multiple abiotic stresses, both in situ and in Physcomitrium patens. The results showed that the ScATG8 gene encoded a protein with a highly conserved ATG8 functional domain. ScATG8 gene was increasingly expressed under different abiotic stresses. Under desiccation stress, the overexpression of ScATG8 enhanced the tolerance of S. caninervis and its ability to scavenge ROS. In addition, ScATG8 overexpression promoted the growth of P. patens under multiple stress conditions. Thus, ScATG8 may be a multifunctional gene, and it plays a critical role in the survival of S. caninervis under various abiotic stresses. Our results provide new insights into the function of ATG8 in enabling desiccation tolerance and open up more possibilities for subsequent plant molecular breeding and the mining of the resistance genes of S. caninervis and other moss species.